THE FRESHWATER FLATFISHES FROM LAMPUNG. SUMATRA. WITH NOTES ON ACHIROIDES LEUCORHYNCHUS BLKR (HETEROSOMATA : SOLEIDAE) - SOETIKNO WIRJOATMODJO (Treubia, 1988)
An account is given on two species of freshwater flat-fish, Achiroides melanorhynchus (Blkr) and A. leucorhyncus Blkr. The eristing description of the latter species is considered inadequate and is hereby corrected based on twelve specimens collected from Lampung, South Sumatra. It is a new locality record for the species as well.